Strategies for Managing Born-Digital Record in University Libraries: A Study of Federal University of Petroleum Resources Effurun - Omosekejimi, Ademola Ferdinand; Eda, Rita (MO.RI Publishing, 2024)
This study used the Federal University of Petroleum Resources, Effurun Library as a case study to investigate strategies for managing born-digital records in the university library. The study aims to ascertain the types of born-digital records available in FUPRE library, the strategies used for managing born-digital records, challenges of managing born-digital records. To achieve these objectives, the descriptive survey research was adopted. This research method was considered appropriate by the researchers because it allows for systematic collection and analysis of data to describe characteristics, behaviors, or opinions within a specific population. Hence it will help to provide insights into the current strategies employed by FUPRE library for managing born-digital records. The questionnaire was the instrument used for data collection and the data collected for the study were analyzed using simple percentages, frequency counts, and bar charts. The study found that: born-digital records such as test-based documents (for example Word documents, and Google documents), etc., library presentations e.g., PowerPoint, spreadsheets e.g., Excel, digital documents e.g., PDFs, and electronic memos are the born-digital records are available in FUPRE library; the only policy in place regarding the management of born-digital records is the policy on storage of born-digital records. The study also found that the library’s strategies for preserving born-digital records are refreshing, migration, and replication and that their strategy for disposing of born-digital records is deletion while the challenges of managing born-digital records are technological obsolescence, lack/poor digital storage facilities, copyright, and intellectual property rights issues among others. These findings contribute to the understanding of current practices and challenges in managing born-digital records within university libraries, specifically at the Federal University of Petroleum Resources Effurun (FUPRE) library. The study recommends that the library management should formulate policies that will cater to the creation/generation, preservation, transfer/exchange as well as the disposition of born-digital records giving them direction when it comes to managing born-digital records in the library among others.